Antifungal potential of yellow bur head limnocharis flava (Buchenau, 1868) against pathogenic oomycete, lagenidium thermophilum - Clarence Jidih; Elliecpearl Jasca Joning; Mohammad Tamrin Mohamad Lal (Borneo Marine Research Institute, UMS, 2023)
Fungal infection by marine oomycetes is the main problem that hinders crustacean production. Therefore, a study to find an alternative fungal treatment that is safer than chemical treatment is currently needed. One of the potential sources of antifungal properties is macrophytes. Limnocharis flava, known as yellow bur head, was found to have antimicrobial properties. Thus, this research was conducted to determine the potential of L. flava extract as an antifungal agent against the marine oomycetes Lagenidium thermophilum IPMB 1801. In this study, ethanol and methanol solvents were used to extract L. flava. The results showed that the methanol extraction yield of L. flava is higher (7.03 g, 35.16%) compared to ethanol extract (3.26 g, 16.26%). The antifungal screening test was conducted using the disc diffusion method. Ethanol and methanol extract of L. flava had antifungal activities against the hyphal growth of L. thermophilum. Continuation from the screening test, the minimum inhibitory concentration for both ethanol and methanol extracts was determined to be at 100 mg/ml respectively. These findings suggest that L. flava has the potential to become an antifungal treatment for the control of fungal infections in the crustacean industry.